A Penalized-Equation-Based Generalized Newton Method for Solving Absolute-Value Linear Complementarity Problems - Yuan Li; Hai-Shan Han; Dan-Dan Yang (Journal of Mathematics)
We consider a class of absolute-value linear complementarity problems. We propose a new approximation reformulation of absolute value linear complementarity problems by using a nonlinear penalized equation. Based on this approximation reformulation, a penalized-equation-based generalized Newton method is proposed for solving the absolute value linear complementary problem. We show that the proposed method is globally and superlinearly convergent when the matrix of complementarity problems is positive definite and its singular values exceed 1. Numerical results show that our proposed method is very effective and efficient.